ADAPTATION OF THE CORN EARWORM SINGLE NUCLEOCAPCIDE NUCLEOPOLYHEDROVIRUS (HELICOVERPA ZEA SNPV) FOR THE CONTROL OF THE COTTON BOLLWORM (HELICOVERPA ARMIGERA) POPULATION - A. V. Kolosov; V. A. Ternovoy; A. N. Shvalov; A. A. Moiseeva; A. S. Safatov; V. N. Mikheev (Вопросы вирусологии, 2017)
Helicoverpa zea (Boddie, 1850) (Hz) single nucleocapcide nucleopolyhedrovirus (SNPV) was adapted to the cotton bollworm (Helicoverpa armigera, (Hübner, 1805) (Ha)) by five blind passages on larvae. The full genomic sequence of the resulting strain HS-18 has been determined (GenBank acc. №: KJ004000.1). Biological activity of the HS-18 strain is higher than the activity of all other Russian strains of NPV, as far as cotton bollworm strain HearSNPV-G4. HS-18-infected caterpillars at the 3-rd and 4-th ages died much faster than those infected with HearSNPV-G4 strain. A major difference of HS-18 genome is an 18 bp repeat in the RING-finger ORF that confirms high variability of this region. Three other insertions and seven base substitutions were observed earlier, while six base substitutions are new. Mutations are located at ORF42, lef-9, ORF58, VP39, PIF-4, P48, SOD, ORF111, ORF129 and ORF138 genes. Among all nucleotide mutation only one is synonymous. Thus we suppose the selective pressure to the virus. The resulting strain HS-18 is recommended as a biopesticide for controlling the number of cotton bollworm in cotton fields.